Policy Interventions for mainstreaming of Small Milk Producers in Contemporary Production System - a Value Chain Analysis of Indian Dairy Sector - Chandel, B. S. (Indian Journal of Dairy Science, 2014)
Milk production in developing countries is dominated by small milk producers. In India, small and marginal farmers contribute the highest (68 %) to the total milk production. However, the scale of milk production per household is very low; 63 % households producing less than or equal to 2.75 litres of milk per day (Birthal, 2008). Â As the consumer preferences and market forces are playing greater role in determining the kind and scale of production, marketing and processing, mainstreaming of small milk producers will ensures livelihood, nutritional and food securities to this vulnerable section of the society. The paper applied value chain analysis to the Indian dairy sector using the approach taken at Institute of Development Studies at University of Sussex, Kaplinsky and Morris (2001) & Schmitz (2005) to identify policy interventions. The value chain approach provides basic understanding needed in designing and implementation of appropriate development programs and policies to support smallholdersâ€™ market participation (Rich et al, 2009). The analysis helps policy maker to (i) identify exogenous variables to stimulate the desired changes, (ii) determine competitiveness and power exercised by different players and (iii) understand the complexity of inter-linkages, in the value chain. The study combines the qualitative and quantitative analysis using data collected from earlier studies, reports and informal interviews. The major policy interventions which emerged from value chain analysis are related to ((1) improving veterinary services especially public and up-gradating local breeds to strengthen milk production capacity of smallholders, (2) strengthening institutional framework to bring small holder under the ambit of organized marketing, (3) modernization of informal sector to reduce transactions cost and handling losses of milk, and (4) encourage fresh milk marketing and clean milk production for quality and demand specific production